Seeding of PMN powders made by the Pechini method - Cavalheiro, A. A.; Foschini, C. R.; Zaghete, M. A.; Paiva-Santos, C. O.; Cilense, M.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2001)
The partial oxalate method, with the columbite route, associated with the Pechini method, was used to obtain a very fine ceramic powder at low temperature. Using this route it was possible to obtain a very reactive powder and to synthesize a lead magnesium niobate (PMN) powder with up to 100% of perovskite phase at a lower temperatures than the PbO melting point. The influence of the BaTiO3 and PbTiO3 seeds in the phase formation, along with time and temperature during the PMN calcination, was also investigated. The amount of 2% of BaTiO3 seeds promoted PMN powder formation with 100% of perovskite phase and a very narrow particle size distribution. (C) 2001 Elsevier B.V. Ltd and Techna S.r.l. All rights reserved.
Keywords: ferroelectric; perovskite; columbite; PMN; seed particles